PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, PERILAKU BELAJAR, DAN LINGKUNGAN BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI DENGAN PERKEMBANGAN TEKNOLOGI SEBAGAI VARIABEL PEMODERASI - Meitha Tyas Utami; Sumaryanto Sumaryanto (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2013)
The level of student understanding of accounting is not only measured byÂ  the intelligence but also the emotional intelligence can be measured, spiritual intelligence, learning behavior, and the learning environment in this study is an independent variable. While the dependent variable is the level of understanding of accounting. Added moderating variable is the development of technology. The study sample of 180 accounting students UGM, STIE YKPN, UPN Veteran Yogyakarta, and UAD taken using purposive sampling technique. Data analysis techniques used in this study is a linear regression, moderated regression analysis, and the Chow test. Result of research indicate that emotional intelligence, spiritual intelligence, behavioral learning, and the learning environment does not affect the level of understanding of accounting, which means that the hypothesis first, second, third, and fourth is unacceptable. In addition, the MRA test results and test results show that the Chow technological developments do not strengthen the relationship between emotional intelligence, spiritual intelligence, behavioral learning, and the learning environment to the level of understanding of accounting, which means that the hypothesis fifth, sixth, seventh, and eighth is not acceptable.